Enhanced precipitation of energetic protons due to Uranus' asymmetric magnetic field - Acevski,M; Masters,A (Geophysical Research Letters, 2024)
Uranus remains one of the most unexplored planets in our solar system, featuring a distinctive magnetic field structure first observed by NASA's Voyager 2 mission almost 40 years ago. Uranus is particularly notable for its pronounced magnetic field asymmetry, a characteristic unique to the icy giants. Here we show that, in the region where Voyager 2 did not pass (< 4 Ru), the asymmetric magnetic field can distort the trajectories of high energy protons within Uranus' radiation belts such that the particles hit the planet when they otherwise would not have (in a traditional dipole field). This implies that radiation belt protons which start with pitch angles well outside their respective loss cones can drift into a region where the loss cone is much bigger and then precipitate. This occurs preferentially in the magnetic north pole due to its significantly weaker surface field strength.